Organizational Innovative Climate and Employees' Improvisational Behavior: The Mediating Role of Psychological Safety and the Moderating Role of Creative Self-Efficacy. (October 2022) - Su, Xiaofeng; Jiang, Xiaoli; Lin, Wenhe; Xu, Anxin; Zheng, Qiujin
Drawing on a perspective grounded in social information processing theory, this paper investigates the mechanism through which organizational innovative climate affects individual improvisational behavior. We developed a theoretical model for analyzing our hypotheses and conducted an empirical study by analyzing data from 356 employees who work for service enterprises. Our paper finds that organizational innovative climate impacts employees' improvisational behavior by triggering their psychological safety perception. It is also found that employee's creative self-efficacy plays a positive moderating role in the relationship between organizational innovative climate and employees' improvisational behavior. The results of our study assert that improvisation is not just an inherently individual phenomenon. Rather, it is also affected by the characteristics of the organizations in which employees are embedded. We discuss the implications of these findings for understanding and promoting employees' improvisational behaviors in the workplace.